The association between stress-induced hyperglycemia ratio and cardiovascular events as well as all-cause mortality in patients with chronic kidney disease and diabetic nephropathy - Boning Cao; Zhendong Guo; Dan-Ting Li; Le-Ying Zhao; Zhen Wang; Ya-Bin Gao; Yao-Xian Wang (Cardiovascular Diabetology)
Abstract The stress hyperglycemia ratio (SHR) is an emerging biomarker used to assess blood glucose levels under acute stress conditions and has been linked to the incidence of adverse clinical outcomes. However, the precise role of SHR in patients with diabetic kidney disease (DKD) and chronic kidney disease (CKD), particularly in relation to mortality, remains poorly understood. This study seeks to investigate the clinical value of SHR as a predictive tool for all-cause and cardiovascular mortality in these patient groups. This study analyzed data from the National Health and Nutrition Examination Survey (NHANES) spanning from 1999 to 2018, encompassing 3,507 individuals diagnosed with diabetic kidney disease (DKD) or chronic kidney disease (CKD). The primary endpoints included all-cause mortality and cardiovascular mortality, with mortality data obtained from the National Death Index (NDI) through December 31, 2019. Participants were categorized into quartiles based on the stress hyperglycemia ratio (SHR), and Cox proportional hazards regression models were employed to examine the association between SHR and mortality. Model 1 did not account for any covariates, Model 2 adjusted for age, sex, and race, while Model 3 additionally incorporated adjustments for educational attainment, marital status, body mass index, smoking behavior, hypertension, hyperlipidemia, and cardiovascular disease. The study comprised 3,507 patients with a mean age of 60.7 years, of whom 56% were female. The overall incidence of all-cause mortality was 38,000 per 100,000 person-years, while cardiovascular mortality was 11,405 per 100,000 person-years. Kaplan–Meier survival analysis revealed that the second quartile of the stress hyperglycemia ratio (SHR) (Q2) exhibited the lowest all-cause mortality (log-rank P = 0.003). Cox regression analysis indicated that the hazard ratio (HR) for all-cause mortality in Q2 was 0.76 (95% CI: 0.63, 0.92), whereas the HR for Q4 was 1.26 (95% CI: 1.04, 1.52). Restricted cubic spline (RCS) analysis revealed a J-shaped association between SHR and all-cause mortality, as well as a U-shaped association with cardiovascular mortality. The minimum risk values for SHR were 0.923 for all-cause mortality and 1.026 for cardiovascular mortality. In patients with diabetic kidney disease (DKD) and chronic kidney disease (CKD), SHR demonstrated a J-shaped relationship with all-cause mortality and a U-shaped relationship with cardiovascular mortality. Subgroup analyses indicated that the effect of spontaneous hypertension on mortality was consistent across all subgroups. This study highlights a significant association between the stress hyperglycemia ratio (SHR) and both all-cause and cardiovascular mortality in patients with diabetic kidney disease (DKD) or chronic kidney disease (CKD). SHR may serve as a critical biomarker for prognostic assessment in these populations, enabling clinicians to identify high-risk patients and tailor personalized treatment strategies that enhance patient quality of life and mitigate mortality risk. Graphical abstract